EFFECTS OF SMALL-SIDED GAMES AND CONVENTIONAL AEROBIC INTERVAL TRAINING ON VARIOUS PHYSIOLOGICAL CHARACTERISTICS AND DEFENSIVE AND OFFENSIVE SKILLS USED IN SOCCER (Kinesiology, 2018)
The aim of this study was to investigate the effects of small-sided game training (SSGT) versus conventional aerobic interval training (CAIT) on soccer-specific endurance performance, lactate threshold levels (mmol·L-1), short-passing ability and defensive and offensive skills of a soccer match. Before and after a 6-week training intervention period, eighteen amateur soccer players (age 21.8±4.8 years) were tested. The tests included the anaerobic threshold (AnT) test, the Yo-Yo Intermittent Recovery Test Level 1 (Yo-Yo IR1), and the Loughborough Soccer Passing Test (LSPT). A manual notational match analysis system was utilized to evaluate the defensive and offensive skills of players during the matches. Both the SSGT and CAIT were performed two days a week and consisted of five sets of 6-minute periods of work at the individualized exercise intensity corresponding to the individual anaerobic threshold, with 3-minute of recovery periods between sets. Mann-Whitney U and Wilcoxon signed rank tests were used to examine the between- and within-group differences, respectively. Statistical analyses revealed that the SSGT group players exhibited significantly better in terms of the LSPT scores (p